Traditional Chinese Medicine nursing management of malignant wounds in a patient with breast cancer (1例乳腺癌癌性伤口患者的中医护理体会) - GAO Shan (高姗); ZHENG Yuhong (郑玉红) (中西医结合护理)
A retrospective analysis was conducted on nursing management of malignant wounds in a patient with breast cancer. Based on the nursing risk assessment and syndrome differentiation, Traditional Chinese Medicine nursing interventions such as emotion regulation, Chinese herbal medicine external application, wound debridement, diet nursing and health guidance were carried out to relieve the pain and swelling, reduce the hemorrhage and improve the skin recovery. (本文总结1例乳腺癌癌性伤口患者的中医护理体会。基于护理评估和辨证分型, 采用情志护理、中药外敷、伤口清创、饮食调护、健康指导等特色护理干预, 有效减轻患者疼痛, 消除肿胀, 改善渗液和出血, 促进皮肤恢复。)